Structural effects of silver-nanoprism-decorated Si nanowires on surface-enhanced Raman scattering. (13th April 2020) - Daoudi, Kais; Gaidi, Mounir; Alawadhi, Hussain; Columbus, Soumya; Zhang, Di; Allagui, Anis; Shameer, Mohamed; Taieb, Aya
Abstract: Surface enhanced Raman scattering (SERS) is an important analytical tool for the optochemical detection of molecules. The enhancement is commonly achieved by engineering (i) novel types and morphologies of plasmonic nanomaterials, and (ii) patterned or roughened supporting substrates of high surface area for increased light scattering and molecule adsorption. Si substrates can be easily and reproducibly textured for effective SERS applications. In this work, silver nanoprisms (AgNPr) coated silicon nanowire (SiNWs) of different morphologies have been prepared by metal-assisted chemical etching and tested for SERS detection of R6G dye. By varying the etching time from 5 to 30 min, the nanowires' lengths increased from 2.4 to 10.5   µ m and resulted in a variable topological morphology of the substrates in terms of bundles and valleys. We found that an optimum of 10 min etching time led to the highest SERS enhancement of R6G on AgNPr/SiNWs at 612 cm −1 Raman shift (30× compared to R6G/Si and 2× compared to R6G/AgNPr/Si), with a detection limit comparable to that of state-of-the-art performances (down to 5×10 −10   M of R6G). Such an enhancement is attributed to a middle ground between increased overall surface area of SiNWs, and the available bundle tops trapping the AgNPr and R6G molecules.